ANALYSIS OF DETRITUS STANDING STOCK IN WESTERN NAYAR RIVER FROM GARHWAL HIMALAYA, UTTARAKHAND - SAGIR, MOHD; RASHID, MOHD; FAROOQ, FASUIL; DOBRIYAL, A. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Detritus is defined as any form of non living organic matter, including different types of plant tissues, animal tissues, dead microbes, faeces as well as products secreted, excreted or exuded from organisms. It serves as a habitat, e g., shelters and breeding sites, etc., and also holds a very important place in food chain, yet are widely neglected by the aquatic biologists. In the present contribution a hypothesis was planned to study the monthly fluctuation in detritus standing stock based on variable riparian vegetation in the river Western Nayar in Garhwal Himalaya, Uttarakhand, India. It was observed that maximum detritus was retained by the stream in a portion where riparian vegetation was dominated by mixed forest and medicinal plants. It was followed by the portion having quercus species as dominant riparian vegetation. Detritus retention in the stream was maximum in winters may be due to low level of current velocity and water temperature. However, due to its high quantity, the periphyton and macrozoobenthic population was also observed high that shows its importance. This is a significant contribution to aquatic study in the region.